The political theory of political thinking : the anatomy of a practice - Freeden, Michael (Oxford University Press, 2013)
What does it mean to say that human beings think politically, and what is distinctive about that kind of thinking? That question is all-too infrequently asked by political theorists, or is dealt with through generalizations, abstractions, and dichotomies. This study examines the actual, real-world patterns people display when thinking politically, identifying six features of political thinking. They include the role of making ultimate decisions and regulating all social affairs, ranking collective priorities, mobilizing support for groups or withholding it, conceptualizing social order and stability as well as disorder and instability, projecting future visions and constructing plans for a society, and engaging the power aspects embedded in language, by means of reason, rhetoric, emotion or menace. Concurrently the untidiness and occasional failures of thinking politically are acknowledged alongside its quest for neatness.